Knowledge management--focus on the knowledge worker - Hortillo, Jose Neil M. (Iloilo City UP Visayas, 2004)
"Knowledge Management focuses on the firm's most important resource, its people. For those in the dark, knowledge management is not a software solution. It means getting the right knowledge (not mere information) to the right people at the right time. To date, organizations have not given much importance to the improvement in efficiency and effectiveness of their knowledge workers because of their ignorance of ways in which knowledge workers communicate and operate through the social processes of collaboration, sharing knowledge and building on each other's ideas. There are four principles of Knowledge Management. It is about: managing people and the knowledge they bring to the workplace; collaboration, teamwork, and nurturing the culture of sharing; synergy of people and technology; and investment in training and retaining knowledge workers. Knowledge workers should learn to collaborate with others without having to fear that the expert knowledge they will share will lessen their competitive advantage."
Keywords: Knowledge management